2006
DOI: 10.1159/000091274
|View full text |Cite
|
Sign up to set email alerts
|

Female Child Sexual Abuse within the Family in a Hungarian County

Abstract: Background: The aim of the study was to analyze the characteristics of intrafamiliar female child sexual abuse and to explore common features that may be utilized as targets for possible methods of prevention. We also described the medical and legal approaches to handling child neglect. Methods: This was a descriptive, cross-sectional study on 52 sexually abused girls under the age of 18 at the Department of Obstetrics and Gynecology, Medical and Health Science Center of Debrecen. We prospectively recorded the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Children from poor families with low level of education and poor social network are more prone to child trafficking, abuse and maltreatment as they can be easily allured in the name of marriage and job offers in the urban areas. 16,32 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Children from poor families with low level of education and poor social network are more prone to child trafficking, abuse and maltreatment as they can be easily allured in the name of marriage and job offers in the urban areas. 16,32 …”
Section: Discussionmentioning
confidence: 99%
“…15 There are also some similarities in the findings of the present study and that of another study with respect to the profile of the perpetrators and the nature of sexual abuse of female children. 16 A review of epidemiological surveys from 21 countries, mainly high and middle-income countries, found that at least 7.0% of females (ranging up to 36.0%) and 3.0% of males (ranging up to 29.0%) reported sexual victimization during adulthood. According to these studies, between 14.0% and 56.0% of the sexual abuse of female children, and up to 25.0% of the sexual abuse of male children, was perpetrated by relatives or step-parents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations